Pengembangan dan Implementasi E-modul Berbasis Discovery learning Terhadap Penguasaan Konsep dan Minat Belajar Peserta Didik SMA - Mohamad Oca Setiawan; Nandang Nandang; Mochammad Taufan (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2025)
The rapid advancement of technology has driven the emergence of various innovations in learning media, particularly in mathematics, a subject often considered difficult for students to understand. This study aimed to develop a Discovery Learning-based e-module on dilation material and to examine its feasibility, practicality, and effectiveness in the learning process. The research employed a Research and Development (R&D) method using the 4D development model, which consists of the Define, Design, Develop, and Disseminate stages. The subjects of this study were 28 eleventh-grade students of SMA Negeri 2 Indramayu. Data were collected using post-tests, interviews, questionnaires, and observations. The validation results indicated that the developed e-module was feasible and practical to use. However, its effectiveness was not optimal due to several constraints, including limited instructional time, varying levels of student readiness, and insufficient supporting facilities.